2002
DOI: 10.2320/matertrans.43.1624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Atmosphere on Void Formation in Copper Interconnects

Abstract: In order to understand the void formation mechanism in electroplated Cu interconnects used in Si-semiconductor devices, microstructure of Cu/CuO/Cu layered films which were prepared on the Si 3 N 4 /Si substrates by the sputter-deposition technique was observed by transmission electron microscopy (TEM) and scanning ion microscopy (SIM). A high density of macro and micro voids were observed in the samples annealed in atmosphere containing hydrogen, whereas no voids were observed in the samples annealed in Ar at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The hydrogen gas evolution from the gold and gold alloy electrodeposits upon annealing at different temperatures is explained in detail elsewhere [25]. The similar type of bubbles/swellings formation in the deposit surface is also observed in Cu interconnects prepared by sputtering after annealing at 400ºC in H 2 /N 2 gas atmosphere [26]. From EBSD data of average grain size, it is confirmed that the average grain size increases from 6 μm to 7 μm on annealing of an as-deposited film at 850ºC for 3 days that indicates onset of grain growth.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The hydrogen gas evolution from the gold and gold alloy electrodeposits upon annealing at different temperatures is explained in detail elsewhere [25]. The similar type of bubbles/swellings formation in the deposit surface is also observed in Cu interconnects prepared by sputtering after annealing at 400ºC in H 2 /N 2 gas atmosphere [26]. From EBSD data of average grain size, it is confirmed that the average grain size increases from 6 μm to 7 μm on annealing of an as-deposited film at 850ºC for 3 days that indicates onset of grain growth.…”
Section: Discussionmentioning
confidence: 63%
“…The earlier study also reported that the void formation on the surface of the sputtered Cu deposit with increasing annealing temperature carried out in H 2 /N 2 gas atmosphere due to high internal pressure stored in the bubbles or swellings [26]. The formation of cracks along the grain boundaries of the swellings are also noticed which is similar to that observed in Cu deposits as well as in hydrogen embrittled bulk Cu materials reported in the previous studies [26,28]. The average grain size increases from 9 μm to 17 μm upon annealing of the as-deposited film from 900ºC to 910ºC for 5 hours.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hence, many investigations to reduce oxidation of Cu seeds layers have been done to prevent void formation in the trenches during electroplating. [9][10][11] For example, the void occurrence rate as a function of the thickness of oxide layer, i.e., holding time after Cu deposition have been investigated and holding time limit has been fixed to reduce void formation in the electroplating process in each manufacturing facilities for practical use. [9][10][11] For barrier metals, it is clearly shown that the thicknesses of barrier metal layers in the trench must be reduced with decreasing interconnect dimension in order to reduce resistivity of Cu wires.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] For example, the void occurrence rate as a function of the thickness of oxide layer, i.e., holding time after Cu deposition have been investigated and holding time limit has been fixed to reduce void formation in the electroplating process in each manufacturing facilities for practical use. [9][10][11] For barrier metals, it is clearly shown that the thicknesses of barrier metal layers in the trench must be reduced with decreasing interconnect dimension in order to reduce resistivity of Cu wires. 12 Barrier metal thickness at the trench is estimated to have a substantial effect on the void formation, because Cu seed layer would not be formed on the defects or voids of barrier metals during sputter deposition leading to the void formation at the trench in the Cu electroplating process.…”
Section: Introductionmentioning
confidence: 99%